Teaching Islamic studies in the age of ISIS, Islamophobia and the Internet - Dorroll, Courtney M.
How can teachers introduce Islam to students when daily media headlines can prejudice students' perception of the subject? Should Islam be taught differently in secular universities than in colleges with a clear faith-based mission? What are strategies for discussing Islam and violence without perpetuating stereotypes? The contributors of Teaching Islamic studies in the age of ISIS, Islamophobia, and the Internet address these challenges head-on and consider approaches to Islamic studies pedagogy, Islamaphobia and violence, and suggestions for how to structure courses. These approaches acknowledge the particular challenges faced when teaching a topic that students might initially fear or distrust. Speaking from their own experience, the contributors include examples of collaborative teaching models, reading and media suggestions, and ideas for group assignments that encourage deeper engagement and broader thinking. They also share personal struggles with confronted with students (including Muslim students) and parents who suspected the courses might have ulterior motives. In an age of stereotypes and misrepresentations of Islam, this book offers a range of means by which teachers can encourage students to thoughtfully engage with the topic of Islam.